The Evolution of the Islamic Education Curriculum: A Comparative Analysis of the Umayyad, Abbasid and Islamic Golden Ages - Faridi; Anugrah Giffari (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to comprehensively analyze the evolution of Islamic education curriculum during the Umayyad Caliphate (661-750 CE), Abbasid Caliphate (750-1258 CE), and the Islamic Golden Age (8th to 14th century). Through a historical-analytical approach with systematic literature review, this research identifies structural and substantial transformations in the Islamic education system, encompassing institutional aspects, teaching methodologies, and knowledge integration. The findings reveal a significant shift from informal mentorship-based education during the Rashidun Caliphate period toward a formal structured educational system during the Umayyad era, which subsequently reached its zenith during the Abbasid period with the establishment of learning institutions such as Bayt al-Hikmah. This study also reveals that the integration of religious education and secular sciences became the primary characteristic of the Islamic curriculum, providing fundamental contributions to the advancement of Islamic civilization and world civilization as a whole. The theoretical and practical implications of these findings are discussed in the context of contemporary Islamic education development.